Eclipse‐Induced Changes to Topside Ion Composition and Field‐Aligned Ion Flows in the August 2017 Solar Eclipse: e‐POP Observations. Issue 20 (18th October 2018) - Yau, Andrew W.; Foss, Victoria; Howarth, Andrew D.; Perry, Gareth W.; Watson, Christopher; Huba, Joseph
Abstract: We present in situ ion composition and velocity measurements during the August 2017 solar eclipse from the Enhanced Polar Outflow Probe (e‐POP), which crossed the path of totality at ~640‐km altitude within 10 min of totality passing. These measurements reveal two distinct H + ion populations, an ~40% decrease in topside plasma density, a similar drop in upward but not downward H + ion flux, and a downward O + ion velocity of ~100 m/s. These features are directly linked to changes in the H + /O + composition and in interhemispheric or field‐aligned light ion flow and to a reduction in the negative spacecraft potential. These observed features were absent on the preceding, noneclipse days and corroborate the reduction in F region plasma density and topside total electron content observed by the Global Positioning System receivers on board. They are attributed to the temporary reduction of photoionization in the eclipsed F region. Plain Language Summary: During a solar eclipse, the Earth's ionosphere undergoes rapid and drastic changes in response to the sudden reduction in solar extreme ultraviolet flux along the eclipse path. The Enhanced Polar Outflow Probe crossed the eclipse path over the State of Idaho within 10 min following totality during the August 2017 Great American Solar Eclipse . Using the ion mass spectrometer and Global Positioning System receivers on board, the Enhanced Polar Outflow Probe observed several important changes in the eclipsed ionosphere, some for the first time, including a rapid ~40% decrease in electron density, an ~100% change in ion composition (H + /O + ratio), and a disruption of light (H + ) ion flow between the eclipsed and opposite hemispheres. These observations demonstrate that in addition to the ionospheric changes, the solar eclipse also induces significant changes to the upper atmosphere (thermosphere) and the plasmasphere. Key Points: Eclipse‐induced decrease in ion density and changes to H + /O + ratio and field‐aligned H + flows were observed within 10 min after totality Eclipse‐induced decrease in only upward (but not downward) H + flux was accompanied by downward O + flow Observed decrease (~40%) in topside plasma density was a factor of ~2 larger than SAMI‐3 prediction